2014
DOI: 10.1039/c4nr02564d
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free synthesis of Cu2ZnSnS4 nanocrystals: a facile, green, up-scalable route for low cost photovoltaic cells

Abstract: Efficient Cu2ZnSnSe4 (CZTSe) solar cells were fabricated with a simple, environmentally friendly, and scalable synthetic method for Cu2ZnSnS4 (CZTS) nanocrystals. CZTS nanoparticles were mechanochemically synthesized from elemental precursors on a relatively large scale (∼20 g), during which no solvents or additives were used, thus alleviating the complex process of particle synthesis. An analysis of the time evolution of the crystalline phase and morphology of precursor powders revealed that the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…As shown in the figure, the phase transformation from CZTS nanocrystals (a few tens of nanometers in size) 17 Another concern over the prolonged annealing of CZTSe and its derivative materials is associated with the local phase decomposition. It has been reported that high-temperature annealing (> 500 °C) causes a loss of Sn, which is attributed to volatile components such as SnSe In a similar way, Sn loss during prolonged annealing would give rise to an accumulation of Zn in the surface region of the present film and hence overall changes in the metal ratio of the resulting of Zn in Figure S2 in the SI).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in the figure, the phase transformation from CZTS nanocrystals (a few tens of nanometers in size) 17 Another concern over the prolonged annealing of CZTSe and its derivative materials is associated with the local phase decomposition. It has been reported that high-temperature annealing (> 500 °C) causes a loss of Sn, which is attributed to volatile components such as SnSe In a similar way, Sn loss during prolonged annealing would give rise to an accumulation of Zn in the surface region of the present film and hence overall changes in the metal ratio of the resulting of Zn in Figure S2 in the SI).…”
Section: Methodsmentioning
confidence: 98%
“…17 In order to produce device-quality CZTSSe absorbers with high crystallinity and a welldeveloped microstructure, a heat treatment of the precursor films at an elevated temperature (> 500 °C) is usually required. However, there are several concerns associated with an intensive heat treatment, which restricts the annealing temperature and duration time.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that this is a result of the exothermic reaction taking place between Sn and CuS, as the latter should be definitely formed after this time of milling [33]. It has to be noted that the rapid consumption of tin was also documented in the synthesis of CZTS nanocrystals, despite the fact that the reaction proceeded more-or-less in a gradual manner until that point [24]. The maximum pressure (1513 mbar) was evidenced after 25 min of milling.…”
Section: Explosive Character Of Synthesismentioning
confidence: 99%
“…The combination of mechanical alloying and spark plasma sintering has documented the possibility to synthesize high-performance thermoelectric materials with the possibility to scale the synthesis process. While CZTS has been already synthesized by a mechanochemical route in 2011 [21] and plenty of papers on this topic have emerged [22][23][24][25][26][27][28][29], literature on Cu 2 FeSn 3 S 8 (CFTS) mechanochemical synthesis is rather scarce. In 2014, an attempt was published to apply mechanochemistry for the synthesis of CFTS [23].…”
Section: Introductionmentioning
confidence: 99%
“…Various precursors were applied-either elements or compounds. As for milling, dry mode 12,13,15,[18][19][20][21][22][23][24][25][26] and wet mode 14,16,17,27 were applied. However, the wet mode was not primarily used for synthesis but rather to improve the homogeneity of already-prepared CZTS applied for subsequent thin film formation.…”
Section: Introductionmentioning
confidence: 99%